Effect Of Price, Product Quality and Service On Vario 150 Motorcycle Sales at Tunas Honda Pramuka Dealer Bandar Lampung - Putra, Chandra Almer; Mega, Selfia Alke (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
PT Astra Honda MotorÂ is a company in charge of manufacturing, assembling and distributing Honda type and brand motorcycles. This company is a company in Indonesia that has rights as an ATPM or Sole Agent for Honda motorcycles. 2001, Knowing that there are limited abilities and time, researchers only see and need to provide clear and focused problem boundaries. So that the problem is limited to discussing only the influence of price, product quality and service on sales of the Honda Vario 150 motorbike at the Honda Tunas Pramuka dealer in Bandar Lampung. In this study using a quantitative method in which the sample in this study amounted to 45 respondents, the analysis technique used was the classical assumption test, multiple linear regression test, with the results of the study that there was an influence between Price on Sales of 25.71%, then the influence between Quality Product on Sales is 69.05%, then the influence between Service on Sales is 39.31% and the influence of the variables Price, Product Quality and Service on Sales is 1.3%. The results of this study are variable X1 (Price), variable X2 (Quality of Products) and variable X3 (Service) significantly influence Sales (Y), of 1.3%, which means that these three variables influence each other and influence one another.